Determination of the effect of sexual assertiveness training on sexual health in married women: A randomized clinical trial - Fatemeh Sayyadi; Nahid Golmakani; Mahdi Ebrahimi; Azadeh Saki; Amin Karimabadi; Faezeh Ghorbani (Wolters Kluwer Medknow Publications, 2019)
Background: Sexual health is a state of physical, mental, and social well-being in relation to sexuality. Sexual assertiveness is a person's ability to meet sexual needs. Considering limited sexual information of women and the taboo nature of talking about sexual needs, the purpose of this study is to evaluate the effectiveness of the sexual assertiveness training on sexual health. Materials and Methods: This randomized clinical trial assignment parallel study with a control group was performed in September and October 2016 on 60 married women referred to Imam Reza Health Center in Mashhad. The sample size was estimated to be 30 subjects per group. Instruments included demographic characteristics, sexual assertiveness, and sexual health questionnaire. The pretest was completed in two groups at the beginning of the study and post-test was done for both groups 1 week after educating the experimental group. Descriptive statistic tests included Chi-square, t-test, and paired t-test, and one-way analysis of variance. A p value less than 0.05 was considered to be statistically significant. Results: The two intervention and control groups showed no significant difference in terms of sexual health level before starting the study (t58 = 0.854, p > 0.05). After the study, based on the independent t-test, the two groups showed significant differences (t58= −4.077, p < 0.001). Conclusions: Sexual assertiveness training can improve women's sexual health. Considering the lack of research in this area and due to the effect of mutual understanding of couples on emotional and sexual issues, further research is necessary for this field.